Pengelolaan Kemandirian Dalam Pembelajaran Ipa Dengan Tutor Sebaya Pada Siswa Kelas Iv Jabal Nur Sekolah Dasar Islam Program Khusus Muhammadiyah Delanggu - WIDIASTUTI, IKA HERNI; , Prof. Dr. Sutama, M.Pd; , Dr. Suyatmini, M.Si (2015)
The purpose of this study was to describe the planning of student independence in learning science by peer tutors, to describe the cultivation of students independence in learning science through habituation with peer tutors, and to describe the evaluation of students independence in learning science by peer tutor in class IV Jabal Nur in Elementary School Islam Program Khusus Muhamamdiyah Delanggu. This type of research is the study of qualitative research design with a case study approach. Data collection technique used observation method, method of interview (interview), and documentation. Data were analyzed using flow model analysis techniques of data collection, data reduction, data presentation, and conclusion. To test the validity of the data used the test of credibility, test of transferability, test of dependability, and the test of confirmability. The results showed that the independence of management are managed by observing the function and purpose of classroom management is done by involving all parties in the learning. For independence in the planning of learning with peer tutors, teachers use lesson plans as a guide in learning. While the independence of the peer tutors planting is done through learning activities carried out in accordance with what is stated in RPP starting from planning, implementation, and evaluation. Regarding the evaluation of independence of students with peer tutors done by post-test and the pre-test to determine the extent to which students understand the learning meteri. While the evaluation of independence carried out by looking at the records held by the teacher.